MEASURING THE FINANCIAL SUSTAINABILITY OF A SAMPLE OF BANKS LISTED ON THE IRAQ STOCK EXCHANGE USING STRESS TESTS - Khalaf Mohammed Hamad; Qassem Mohammed Mikhlif (Scholar Express Journals, 2023)
The subject of the financial sustainability of the banking system receives great attention from specialists in this field, as the repeated crises that the banking system was exposed to showed that measuring the financial sustainability of banks and their ability to face crises is not an easy matter, therefore, this study sought to measure financial sustainability indicators represented by ( capital adequacy and the index of sustainability, liquidity and profitability), and an indication of the basic stages through which the process of applying stress tests goes through and an indication of their role in achieving financial sustainability, as well as an explanation of questions about the possibility of relying on stress tests in measuring the financial sustainability of banks and determining their ability to withstand shocks, and knowing the change in Indicators of financial sustainability in the event of scenarios of different severity (least severe, medium severity, most severe), and the study sample included a number of Iraqi commercial banks listed in the Iraq Stock Exchange, amounting to (3) banks and for the period (2011-2021).
Keywords: financial sustainability; stress tests